Global cost of correcting vision impairment from uncorrected refractive error - TR Fricke; BA Holden; DA Wilson; G Schlenther; KS Naidoo; S Resnikoff; KD Frick (The World Health Organization, 2012)
OBJECTIVE: To estimate the global cost of establishing and operating the educational and refractive care facilities required to provide care to all individuals who currently have vision impairment resulting from uncorrected refractive error (URE). METHODS: The global cost of correcting URE was estimated using data on the population, the prevalence of URE and the number of existing refractive care practitioners in individual countries, the cost of establishing and operating educational programmes for practitioners and the cost of establishing and operating refractive care facilities. The assumptions made ensured that costs were not underestimated and an upper limit to the costs was derived using the most expensive extreme for each assumption. FINDINGS: There were an estimated 158 million cases of distance vision impairment and 544 million cases of near vision impairment caused by URE worldwide in 2007. Approximately 47 000 additional full-time functional clinical refractionists and 18 000 ophthalmic dispensers would be required to provide refractive care services for these individuals. The global cost of educating the additional personnel and of establishing, maintaining and operating the refractive care facilities needed was estimated to be around 20 000 million United States dollars (US$) and the upper-limit cost was US$ 28 000 million. The estimated loss in global gross domestic product due to distance vision impairment caused by URE was US$ 202 000 million annually. CONCLUSION: The cost of establishing and operating the educational and refractive care facilities required to deal with vision impairment resulting from URE was a small proportion of the global loss in productivity associated with that vision impairment.